The necessity of revision and reform in Iran pharmacy education: Finding a way for evolution - Seyed Mohammad Iman Moezzi; Sadra Nadimi Parashkouhi; Hosein Abbasi; Amir Azadi; Abdolali Mohagheghzadeh; Mehrdad Hamidi (Shiraz University of Medical Sciences, 2021)
The pharmaceutical profession has long been recognized as one of the key components of health systems. Pharmacists are playing roles in various aspects of health care, including production, distribution, and rational monitoring of drug use by patients. The training of efficient manpower is one of the most important goals of those in charge of training in this discipline. Because of different challenges that pharmacy education is facing including its inadequacy for professional directing, irrelevancy to future roles, improper position of pharmacists in the health system, and lack of many pharmacy-based services, education professionals agree on the need to revise the curriculum. It is necessary to obtain comprehensive information on the current state of pharmacy education before revision and reform, and act based on shreds of evidence and domestic priorities. In this article, we aim to explain the necessity of revision of pharmacy education and pharmacy curriculum as its core. We try to explain our idea of the corrective plan and the considerations.